2022
DOI: 10.1186/s40104-022-00684-5
|View full text |Cite
|
Sign up to set email alerts
|

Genomic patterns of homozygosity and inbreeding depression in Murciano-Granadina goats

Abstract: Background Inbreeding depression can adversely affect traits related to fitness, reproduction and productive performance. Although current research suggests that inbreeding levels are generally low in most goat breeds, the impact of inbreeding depression on phenotypes of economic interest has only been investigated in a few studies based on genealogical data. Results We genotyped 1040 goats with the Goat SNP50 BeadChip. This information was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 104 publications
1
9
0
Order By: Relevance
“…The whole population averaged 28 ROH with a length of 3.14 Mb. Similar results were observed in goat breeds characterized by average values of inbreeding (Cortellari et al, 2021;Luigi-Sierra et al, 2022). However, the separate analysis of HI and LI animals showed large differences in the number and average length of ROH segments in HI compared with LI.…”
Section: Hi and LI Individualssupporting
confidence: 83%
See 2 more Smart Citations
“…The whole population averaged 28 ROH with a length of 3.14 Mb. Similar results were observed in goat breeds characterized by average values of inbreeding (Cortellari et al, 2021;Luigi-Sierra et al, 2022). However, the separate analysis of HI and LI animals showed large differences in the number and average length of ROH segments in HI compared with LI.…”
Section: Hi and LI Individualssupporting
confidence: 83%
“…Its negative consequences are evidenced mainly in traits related to fertility and adaptation to environmental stress (Doekes et al, 2021). Despite the importance of such traits in extensive production systems, specific studies assessing inbreeding in goats are still scarce (Dadousis et al, 2021; Luigi‐Sierra et al, 2022; Oget et al, 2019; Onzima et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several studies showed that inbreeding based on ROH provides a better measure of individual inbreeding than using pedigree information (Ferenčaković et al, 2013b ; Forutan et al, 2018 ). Thus, F ROH has been largely adopted as inbreeding coefficient to study depression phenomena in cattle (e.g., Doekes et al, 2019 ; Hidalgo et al, 2021 ; Pilon et al, 2021 ), sheep (Antonios et al, 2021 ; Tao et al, 2021a ) and goat (Luigi‐Sierra et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated the growing applicability of genomic inbreeding in both wild and domestic populations (e.g., Antonios et al, 2021;Foster et al, 2021;Gagnon et al, 2019;Luigi-Sierra et al, 2022;Saura et al, 2015;Townsend & Jamieson, 2013).…”
Section: Introductionmentioning
confidence: 99%